Performance of growing and finishing dairy bulls offered diets based on whole-crop barley silage with or without protein supplementation relative to a grass silage-based diet - Arto Kalevi Huuskonen (Agricultural and Food Science, 2013)
This study was conducted to examine the performance of growing dairy bulls offered diets based on whole-crop barley silage with or without protein supplementation when compared to a grass silage-based diet. A feeding experiment comprised 36 bulls which were fed a total mixed ration ad libitum. The four dietary treatments were: 1) grass silage (600 g kg-1 dry matter) and rolled barley (400), 2) whole-crop barley silage (600) and rolled barley (400), 3) whole-crop barley silage (600), rolled barley (310) and rapeseed meal-based protein supplementation (90), and 4) whole-crop barley silage (600), rolled barley (330) and rapeseed meal + urea -based protein supplementation (70). Replacing grass silage with whole-crop barley decreased the carcass gain and carcass weight of the bulls due to lower energy intake. Protein supplementation either as rapeseed meal or rapeseed meal + urea of whole-crop barley silage based diets had no effects on animal performance.